2006 IEEE/RSJ International Conference on Intelligent Robots and Systems 2006
DOI: 10.1109/iros.2006.282353
|View full text |Cite
|
Sign up to set email alerts
|

Detection Threshold and Mechanical Impedance of the Hand in a Pen-Hold Posture

Abstract: -We report position and force detection thresholds for sinusoidal waveforms in the frequency range 10-500 Hz delivered through a stylus. The participants were required to hold the stylus in a way similar to that of holding the stylus of a force-feedback device. A minishaker moved the stylus along its length so that the majority of vibrations were presented tangentially to the skin of the hand. The measured position thresholds decreased initially with an increasing stimulus frequency and formed a U-shaped curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 19 publications
7
30
1
Order By: Relevance
“…Brisben et al reported the displacement detection thresholds for a cylindrical tool that was held in the palm of the hand in a power grip and vibrated in a direction tangential to the skin of the palm [9]. One of our previous studies published the displacement and force detection thresholds measured with a stylus held in a pen-holding posture [1]. In the present study, we investigated the detection thresholds for a spherical tool held with multiple fingers.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Brisben et al reported the displacement detection thresholds for a cylindrical tool that was held in the palm of the hand in a power grip and vibrated in a direction tangential to the skin of the palm [9]. One of our previous studies published the displacement and force detection thresholds measured with a stylus held in a pen-holding posture [1]. In the present study, we investigated the detection thresholds for a spherical tool held with multiple fingers.…”
Section: Introductionmentioning
confidence: 92%
“…Common tool shapes include stylus, thimble, puck and ball, resulting in varying hand-holding postures and contact areas with the tool. We have been interested in examining the effect of tool shapes on the proximal stimuli received by the fingers of the hand (e.g., [1]). The present study considers the spherical tool (e.g., a ball or a puck), found in the Delta or Omega devices (ForceDimension, Switzerland) and magnetic levitation devices [2], that is typically held in the hand with multiple fingertips.…”
Section: Introductionmentioning
confidence: 99%
“…McMahan and Kuchenbecker identified a five-parameter MSD model of the hand interfaced with a stylus grip haptic device using a 1-DOF linear actuator custom mounted onto the Phantom's stylus itself (for high-frequency, i.e., 10-200 Hz, vibrotactile feedback applications) [22]. Israr et al have used both stylus-based devices and spherical actuators to shake the hand at 10-500 Hz [23], [24]. Also, Díaz and Gil have investigated the vibration modes from 0.7 to 200 Hz in 1 DOF of the human operator using a racquet grip on the Phantom Premium 1.0 and a custom haptic interface [25].…”
Section: Introductionmentioning
confidence: 99%
“…12) and the rotated angle of the pen (φ in Fig. 12) was used as an indicator of solidity [29,30]. The system for simultaneously measuring force and position data is shown in Fig.…”
Section: Solidity Performance Experimental Data Analysis Methodsmentioning
confidence: 99%